Influence of gravimetric water content of a debris material on downslope propagation characteristics by laboratory flume tests - Sandaruwan Karunarathna; Satoshi Goto (Geoenvironmental Disasters)
Abstract Background Landslides can be simply defined as unstable mass movements in a slope due to gravity. Initiation of a landslide occurs when the critical combination of internal and external terrain factors of a slope is combined with a triggering event. After the initiation, the unstable mass propagates downstream until the mass stabilizes. Surface morphology of the downstream, fluid motion characteristics of the unstable mass, and obstacle characteristics controlled the propagation of failed mass. The surface morphology and the obstacle characteristics can be precisely obtained by the high-resolution surface raster data. The fluid motion characteristics of unstable mass are highly controlled by the water content and the particle size distribution of failed mass. The influence of the water content of failed mass with different flow angles and depositional angles is highly required to understand the downslope propagation characteristics. A specially designed flume test apparatus was used to examine the behavior of the landslide fluid propagation characteristics. The soil for the flume test was prepared related to the debris from the Aranayake landslide in Sri Lanka. Downslope propagations with different water contents, flow angles, and deposition angles were expected to be examined. This paper discussed the results obtained from the flume tests with the different water contents and different flow angles to the horizontal deposition. Results Two interests of the propagation characteristics were focused. First, the Mobility Index of debris with water content was systematically examined. The water content and the Mobility Index indicated the positive power type relationship. This relationship shifted with the changing of the flow angle. Second, the horizontal spreading deposition was examined. The quadratic type relationship was obtained to the relationship between directional spreading weightings on the horizontal plane and flow angles. This relationship was shifted with the changing of water content. Conclusions The specially designed flume test yielded successful results for the influence of water content on the downslope propagation characteristics of a failure mass. These results were planned to be used for the computer-based downslope propagation simulation model development by the combined approach of Cellular Automaton and Multi-Agents models.